Adaptation of an in vitro one-compartment pharmacodynamic chemostat for testing efficacy of ceftazidime against Burkholderia pseudomallei outside a BSL3 facility - Hana Farizah Zamri; Mohammad Ridhuan Mohd Ali; Ahmad Izzan Irfan Sha'ari; Nurul Husna Mohd Mazalan; Norazah Ahmad; Nur Asyura Nor Amdan; Nusaibah Abdul Rahim; Zakuan Zainy Deris (MethodsX)
Non-clinical pharmacokinetic-pharmacodynamic (PKPD) models are crucial in the initial design of drug-dosage regimens and in drug development but has rarely been employed for testing high-risk organisms due to stringent handling procedures. Burkholderia pseudomallei is classified as a Tier 1 select agent with international guidelines recommending this organism to be handled within a biosafety level 3 (BSL3) facility. Unfortunately, BSL3 facilities are not widely available in low-resource settings. This paper describes a detailed guide for setting up an in vitro pharmacodynamic infection model specific for testing B. pseudomallei outside BSL 3 laboratory. Briefly in this study, • All procedures involving active handling of live B. pseudomallei cultures were performed strictly inside a class II BSC in BSL-2 plus negative airflow laboratory. • The model was set to simulate B. pseudomallei-bacteremia treated with ceftazidime, a 1st-line anti-melioidosis drug with an approximate 2-hour half-life. Model validation was performed by simulating ceftazidime half-life. • For the pharmacodynamic study, ceftazidime was given as bolus injections at 8-hour intervals into the central culture chamber containing actively growing B. pseudomallei.